2017
DOI: 10.1016/j.watres.2017.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of drinking water quality at the tap using fluorescence spectroscopy

Abstract: Treated drinking water may become contaminated while travelling in the distribution system on the way to consumers. Elevated dissolved organic matter (DOM) at the tap relative to the water leaving the treatment plant is a potential indicator of contamination, and can be measured sensitively, inexpensively and potentially on-line via fluorescence and absorbance spectroscopy. Detecting elevated DOM requires potential contamination events to be distinguished from natural fluctuations in the system, but how much n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(49 citation statements)
references
References 34 publications
2
47
0
Order By: Relevance
“…Some of the recent water quality studies include: an assessment of trace elements in surface and ground water quality in the Ebocha-Obrikom oil and gas producing area of Rivers State, Nigeria by Raimi and Sabinus (2017) [1]; Morufu and Clinton, (2017) [2], water-related problems and health conditions in the oil producing communities in central senatorial district of Bayelsa State by Raimi et al (2017) [3], water quality on intermittent water supply by Erickson et al (2017) [4], major ion chemistry of the groundwater by Bikundia and Mohan (2014) [5], water quality due to temperature variation and water stagnation by Zlatanoviae et al (2017) [6], the use of fluorescence spectroscopy for tap water quality assessment by Heibati et al (2017) [7], Hydrochemical evolution and quality of groundwater by Jassas and Merkel (2015) [8], and evaluation of hydrogeology and groundwater quality by Edet (2016) [9]. Water quality was also studied in different areas of the world by Dhamodharan et al (2016) [10], Li et al (2016) [11], Nagaraju et al (2016) [12], Kumar et al (2017) [13], and Tiwari et al (2017) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the recent water quality studies include: an assessment of trace elements in surface and ground water quality in the Ebocha-Obrikom oil and gas producing area of Rivers State, Nigeria by Raimi and Sabinus (2017) [1]; Morufu and Clinton, (2017) [2], water-related problems and health conditions in the oil producing communities in central senatorial district of Bayelsa State by Raimi et al (2017) [3], water quality on intermittent water supply by Erickson et al (2017) [4], major ion chemistry of the groundwater by Bikundia and Mohan (2014) [5], water quality due to temperature variation and water stagnation by Zlatanoviae et al (2017) [6], the use of fluorescence spectroscopy for tap water quality assessment by Heibati et al (2017) [7], Hydrochemical evolution and quality of groundwater by Jassas and Merkel (2015) [8], and evaluation of hydrogeology and groundwater quality by Edet (2016) [9]. Water quality was also studied in different areas of the world by Dhamodharan et al (2016) [10], Li et al (2016) [11], Nagaraju et al (2016) [12], Kumar et al (2017) [13], and Tiwari et al (2017) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Further, studies have demonstrated that discharges from STWs impact downstream environmental compartments. Heibati et al () have used fluorescence spectroscopy to detect sewage‐derived dissolved organic carbon (DOC) in domestic tap water, whereas Tedetti, Cuet, Guigue, and Goutx () have used fluorescence spectroscopy to show that sewage DOC could be detected in a coral reef.…”
Section: Introductionmentioning
confidence: 99%
“…Deployment of suitable water treatment strategies and evaluation of their effectiveness rests upon analytical determination of concerned contaminants. Current established techniques include atomic absorption spectrophotometry [1,2], ion chromatography [3,4], inductively coupled plasma-mass spectrometry [5,6], potentiometry [7,8], UV-Vis spectrophotometry [9], and fluorescence spectroscopy [10]. Even though these stateof-the-art methods are precise and accurate, most of them are time-consuming and expensive, and require special sample preparation procedures to be carried out by trained personnel.…”
Section: Introductionmentioning
confidence: 99%